2018
DOI: 10.1016/j.theriogenology.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Placental development during early pregnancy in sheep: Progesterone and estrogen receptor protein expression

Abstract: The aim of this study was to evaluate the pattern of protein expression of the steroid receptor isoforms of nuclear progesterone receptors (PGR) A and B, and estrogen receptors (ESR1 and 2) in utero-placental compartments during early pregnancy. Utero-placental tissues were collected from days 14-30 (n = 4 ewes/day), and uterine tissues were collected from non-pregnant ewes on day 10 after estrus (n = 4). Cross sections of formalin-fixed and paraffin embedded tissues were immunofluorescently stained to detect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 67 publications
2
18
0
Order By: Relevance
“…A loss of PR has been suggested to support embryo development and implantation [9]. In cattle, the loss of the PR protein in the LE and GE is observed from day 12/13 of the cycle and during pregnancy [5,6], whereas in pregnant sheep, this takes place from day 14 onward [7]. This might indicate that the loss of the LE PR in the roe deer takes place before diapause or is associated with the induction of diapause.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A loss of PR has been suggested to support embryo development and implantation [9]. In cattle, the loss of the PR protein in the LE and GE is observed from day 12/13 of the cycle and during pregnancy [5,6], whereas in pregnant sheep, this takes place from day 14 onward [7]. This might indicate that the loss of the LE PR in the roe deer takes place before diapause or is associated with the induction of diapause.…”
Section: Discussionmentioning
confidence: 99%
“…During preimplantation embryo development, ovarian progesterone (P4) stimulates the secretory function of the endometrial LE and GE. Although the P4 concentration remains high during the luteal phase and early pregnancy in ruminants [5][6][7], the LE and GE gradually loose the expression of the progesterone receptor (PR) from days 12 to 14 onward during both the normal cycle and pregnancy [5][6][7]. Upon loss of the PR in the LE and GE, P4 is known to act indirectly via PR expressed on stromal cells and the induction of progestamedins [8].…”
Section: Introductionmentioning
confidence: 99%
“…Several processes which are critical for pregnancy establishment take place during early pregnancy including implantation, placentation, and initiation of fetal and placental growth [13]. We have recently demonstrated that expression of steroid hormone receptors and factors involved in the regulation of growth and angiogenesis change dramatically during early pregnancy, and are affected by pregnancy stage and embryo origin [49].…”
Section: Introductionmentioning
confidence: 99%
“…Steroid hormones exert their direct effects through nuclear and membrane receptors [1012]. Uterine and placental expression of estrogen and progesterone receptors (ER and PR, respectively) has been well described for numerous species [3,8,9,1014]. Steroid receptors are expressed in several uterine and placental compartments, and their expression is regulated by estradiol-17β (E2), progesterone (P4) and other regulatory factors [11].…”
Section: Introductionmentioning
confidence: 99%
“…In general, progesterone blocks the sexual behavior induced by estradiol in female sheep [14] . Estrogen and progesterone regulate the uterine endocrine and paracrine signals through their receptors during the estrus cycle and pregnancy in sheep [15,16] . There was no study on PMSG-estrus induction during estrus interval after lambing in spring in Small-tail Han sheep.…”
Section: Introductionmentioning
confidence: 99%